Identification of QTL for alkylresorcinols in wheat and development of KASP markers for marker-assisted selection of health-promoting varieties - Lei Zhi; Xue Gong; Hongyu Zhang; Jindong Liu; Shuanghe Cao; Yong Zhang; Jun Yan; Wenfei Tian; He Zhonghu (American Chemical Society, 2024)
This study evaluated alkylresorcinol concentration (ARC) in recombinant inbred lines (RILs) from the cross of Zhongmai 578 and Jimai 22 in three environments. ARC exhibited a continuous distribution ranging from 337.4 to 758.0, 495.4–768.0, and 456.3–764.7 μg/g, respectively, in three environments. Analysis of variance (ANOVA) indicated significant (P < 0.001) impacts of genotypes, environments, and their interactions. The broad-sense heritability of ARC was 0.76. Genome-wide linkage mapping analysis identified four stable quantitative trait loci (QTL) for ARC on chromosomes 2A, 3A, 4D, and 7A. Kompetitive allele-specific PCR (KASP) marker of each QTL was developed and validated in 206 representative wheat varieties. Wheat varieties harboring 0, 1, 2, 3, and 4 favorable alleles had ARC of 499.1, 587.8, 644.7, 668.5, and 711.1 μg/g, respectively. This study suggests that combining multiple minor-effect QTL through KASP markers can serve as an effective strategy for breeding high-ARC wheat, thereby enhancing innovations in functional food production.